But who will guard the custodians themselves (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2014)
This article analyzes the legal issues regarding intelligence services by examining the foundations of its presence in the Constitutional State. Juridical elementswill determinate in each case the organization, duties and oversight of the intelligence services. In this way, specific foundations that can be found in Spanish Law to regulate intelligence services are expounded.
Keywords: Intelligence services; regulation; juridical foundations; legal issues; oversight.